2005
DOI: 10.1063/1.2064307
|View full text |Cite|
|
Sign up to set email alerts
|

Optoelectronic properties of polymer-nanocrystal composites active at near-infrared wavelengths

Abstract: We report a systematic study of the optoelectronic processes occurring in composites made of near-infrared (IR) emitting nanocrystals and conjugated polymers. We focus on PbSe and InAs∕ZnSe blended with polyphenylenevinylene-type polymers. We find that the process responsible for quenching the visible luminescence of the polymer by the nanocrystal varies depending on the nanocrystal composite. Moreover, the high (66%) energy-transfer efficiency from the polymer to the PbSe nanocrystal does result in significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Filling of these traps is necessary to achieve a flow of carriers through the full layer thickness to the interface, resulting in an increase of the turn-on voltage. These effects are in agreement with experimental observations [33][34][35][36]. Fig.…”
Section: Simulation Resultssupporting
confidence: 94%
“…Filling of these traps is necessary to achieve a flow of carriers through the full layer thickness to the interface, resulting in an increase of the turn-on voltage. These effects are in agreement with experimental observations [33][34][35][36]. Fig.…”
Section: Simulation Resultssupporting
confidence: 94%
“…It is attractive in various applications such as laser materials [4], solar cells [5], infrared detectors [6], near-IR luminescence [7] and thermoelectric devices [8]. In the past few years, various methods including sonochemical synthesis [9], hydrothermal/solvothermal synthesis [10,11] and chemical bath deposition method [12] have been used to prepare PbSe nanocrystals since they are able to the control over size and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…MEH-PPV is the most common polymer used as host in hybrid lightabsorbing or -emitting devices. [136][137][138][139][140] Some authors reported yellow-PPV, 140 CN-PPV 141,142 or methylsubstituted ladder-type poly(paraphenylene) (MeLPPP) 143 as hosts (Fig. 7).…”
Section: Technology Driven Exploration Of Hybrid Materialsmentioning
confidence: 99%